Shifting foundations: understanding the relationship between John Cassian and Evagrius Ponticus - Hager Conroy, K (2014)
John Cassian is an Eastern-educated monk writing in the early fifth century for the monks of Gaul and is crucial to the development of Western monasticism through the transmission of Greek ascetic ideas to the Latin West. He is heavily influenced by the teachings of Evagrius Ponticus, a prolific late fourth-century Egyptian monk crucial to the development of Christian mysticism; however, there has been no clear line drawn between the influence of Evagrius and Cassian's own originality. While Cassian uses Evagrian asceticism to the fullest, he nevertheless places it onto a divergent theological foundation which fundamentally alters that inherited asceticism. Evagrius' asceticism is shaped by his anthropology, cosmology, soteriology, and eschatology – all of which are based on his understanding of Creation and Christology. The monk working through Evagrius' asceticism sees the world and all the divisions in it—e.g. body/soul, human/angel/demon, vice/virtue—as a temporary construct which facilitates the eventual obliteration of all divisions through salvation – including divisions between good and evil. Cassian, however, writes twenty years after Evagrius’ death and in a changed theological atmosphere, in which Evagrius' basic premises have become more controversial. Cassian is able to work an ascetic program previously defined by Evagrian theology into a legitimate and coherent asceticism based on a different understanding of Creation. This resembles Evagrius' asceticism to such an extent, that he has been called "merely a Latin translator". However, through fleshing out and comparing Cassian's understanding of the practical, the eight principal vices, the spiritual battle, and the contemplative life, it becomes clear that Cassian has a fundamentally different understanding of Creation and Christology, and this changes the relationship between body and soul, created and Creator, and corruption and salvation – all fundamental areas in an effective and coherent asceticism. Therefore, although the frame of his asceticism is Evagrian, the theological underpinnings of that asceticism create a vastly different experience for the monk through a different definition of humanity and the relationship between created and Creator.